Concomitant medication polypharmacy, interactions and imperfect adherence are common in Australian adults on suppressive antiretroviral therapy. (2nd January 2018) - Siefried, Krista J.; Mao, Limin; Cysique, Lucette A.; Rule, John; Giles, Michelle L.; Smith, Don E.; McMahon, James; Read, Tim R.; Ooi, Catriona; Tee, Ban K.; Bloch, Mark; de Wit, John; et al.
Abstract : Objectives: We quantified concomitant medication polypharmacy, pharmacokinetic and pharmacodynamic interactions, adverse effects and adherence in Australian adults on effective antiretroviral therapy. Design: Cross-sectional. Methods: Patients recruited into a nationwide cohort and assessed for prevalence and type of concomitant medication (including polypharmacy, defined as ≥5 concomitant medications), pharmacokinetic or pharmacodynamic interactions, potential concomitant medication adverse effects and concomitant medication adherence. Factors associated with concomitant medication polypharmacy and with imperfect adherence were identified using multivariable logistic regression. Results: Of 522 participants, 392 (75%) took a concomitant medication (mostly cardiovascular, nonprescription or antidepressant). Overall, 280 participants (54%) had polypharmacy of concomitant medications and/or a drug interaction or contraindication. Polypharmacy was present in 122 (23%) and independently associated with clinical trial participation, renal impairment, major comorbidity, hospital/general practice-based HIV care (versus sexual health clinic) and benzodiazepine use. Seventeen participants (3%) took at least one concomitant medication contraindicated with their antiretroviral therapy, and 237 (45%) had at least one pharmacokinetic/pharmacodynamic interaction. Concomitant medication use was significantly associated with sleep disturbance and myalgia, and polypharmacy of concomitant medications with diarrhoea, fatigue, myalgia and peripheral neuropathy. Sixty participants (12%) reported imperfect concomitant medication adherence, independently associated with requiring financial support, foregoing necessities for financial reasons, good/very good self-reported general health and at least 1 bed day for illness in the previous 12 months. Conclusion: In a resource-rich setting with universal healthcare access, the majority of this sample took a concomitant medication. Over half had at least one of concomitant medication polypharmacy, pharmacokinetic or pharmacodynamic interaction. Concomitant medication use was associated with several adverse clinical outcomes. Abstract : Supplemental Digital Content is available in the text